2010
DOI: 10.1074/jbc.m109.041913
|View full text |Cite
|
Sign up to set email alerts
|

The Insulin-like Growth Factor-1 Binding Protein Acid-labile Subunit Alters Mesenchymal Stromal Cell Fate

Abstract: Age-related osteoporosis is accompanied by an increase in marrow adiposity and a reduction in serum insulin-like growth factor-1 (IGF-1) and the binding proteins that stabilize IGF-1. To determine the relationship between these proteins and bone marrow adiposity, we evaluated the adipogenic potential of marrow-derived mesenchymal stromal cells (MSCs) from mice with decreased serum IGF-1 due to knockdown of IGF-1 production by the liver or knock-out of the binding proteins. We employed 10 -16-week-old, liver-sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 37 publications
3
10
0
1
Order By: Relevance
“…We found that ALSKO mice had significantly lower osteoclast number formed in vitro than WT cultures. These results are in agreement with our previous studies showing impaired osteoclastogenesis in bone marrow extracted from young ALSKO mice (Fritton et al 2010;Yakar et al 2009b). …”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…We found that ALSKO mice had significantly lower osteoclast number formed in vitro than WT cultures. These results are in agreement with our previous studies showing impaired osteoclastogenesis in bone marrow extracted from young ALSKO mice (Fritton et al 2010;Yakar et al 2009b). …”
Section: Discussionsupporting
confidence: 94%
“…4). These findings are in agreement with our previous study, showing decreased osteoclastogenesis in ALSKO mice during growth (Fritton et al 2010).…”
Section: Effects Of Decreases In Serum Igf-1 On Bone Remodeling Durinsupporting
confidence: 94%
“…The effects of IGFBP-3 on adipocyte differentiation have been variable. IGFBP-3 deficiency or hIGFBP-3 supplementation did not affect bone marrow adipocytes in culture (43), whereas hIGFBP-3 inhibited the differentiation of 3T3-L1 cells and rat preadipocytes in vitro (39,42). In contrast, hIGFBP-3 enhanced adipocyte differentiation and stimulated the lipogenic enzyme glycerol-3-phosphate dehydrogenase in visceral and sc preadipocytes (44).…”
Section: Discussionmentioning
confidence: 87%
“…Remarkably, aging PGKmutBP3 mice had reduced expression of the BAT signature UCP1, which was not expected in the presence of increased free IGF-1, because IGF-1 plays an important role in the thermogenic differentiation of brown adipocytes (16,17). Impaired integration of IGF-1 into ternary complex formation may provide an alternative explanation, given the similarity between bone marrow adipocytes and BAT (43). To determine whether IGF-1 expression is altered in BAT, we measured IGF-1 mRNA ex vivo.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation